Consumption Work in the circular economy: A research agenda. (25th October 2021) - Hobson, Kersty; Holmes, Helen; Welch, Dan; Wheeler, Katy; Wieser, Harald
Abstract: Circular Economy frameworks have become central to debates and interventions that aim to reduce global resource use and environmental despoilment. As pathways to both systemic and micro-scale transformations, there remain many challenges to making Circular Economy actionable. One such challenge is facilitating the emergence of the 'circular consumer'. Here, we are all encouraged to shift everyday practices to consume new products and services and/or participate in the 'Sharing Economy': all of which are claimed, in some prominent debates, to automatically offer more 'convenience' for the consumer. In response, this paper argues that viewing such debates through the lens of Consumption Work offers a different picture of what it takes to be, and what we need to know about, the circular consumer. Consumption Work refers to the labour integral to the purchase, use, re-use and disposal of goods and services. This paper argues that the nature and scope of such work has been underplayed in Circular Economy debates to date, and that becoming a circular consumer requires varied and unevenly distributed forms of Consumption Work, which in turn, has significant implications for the success of Circular Economy. This paper thus proposes a research agenda into this topic, outlining five, inter-related, critical issues that a Circular Economy research agenda must address, including questions of who undertakes Consumption Work; to what ends; and how its multiple forms are coordinated within and beyond the household. Highlights: The concept of Consumption Work provides a novel lens for Circular Economy research. It highlights the time, skills and access needed to participate in 'circular consumption'. This paper outlines a Consumption Work research agenda for the Circular Economy. This agenda will address current gaps in vital Circular Economy research.